2009
DOI: 10.1093/jac/dkp122
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of Escherichia coli producing extended-spectrum β-lactamases in Lugo (Spain): dissemination of clone O25b:H4-ST131 producing CTX-M-15

Abstract: CTX-M-type ESBLs, primarily CTX-M-14 and CTX-M-15, have emerged as the predominant types of ESBL produced by E. coli isolates in Lugo. In view of the reported findings, long-term care facilities for elderly people may represent a significant reservoir for E. coli clone O25b:H4-ST131 producing CTX-M-15. The triplex PCR developed in this work will be useful for rapid and simple detection of this clone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
76
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(87 citation statements)
references
References 20 publications
9
76
1
Order By: Relevance
“…We identified two intestinal AIEC strains and one extraintestinal AIEC strain, all of which were of the O25:H4 serotype, that belonged to the emerging and virulent clonal group ST131 (6,14,26,31,42). Currently, this clonal pathotype is the most prevalent among human ExPEC strains.…”
Section: Discussionmentioning
confidence: 99%
“…We identified two intestinal AIEC strains and one extraintestinal AIEC strain, all of which were of the O25:H4 serotype, that belonged to the emerging and virulent clonal group ST131 (6,14,26,31,42). Currently, this clonal pathotype is the most prevalent among human ExPEC strains.…”
Section: Discussionmentioning
confidence: 99%
“…This clonal group is an emerging human pathogen in many parts of the world, including continental Europe (3,33), the United Kingdom (28), Turkey (52), Korea (30), Canada (36,38), and the United States (18,19). Its association with bla CTX-M-15 , which encodes the CTX-M-15 extended-spectrum ␤-lactamase (ESBL), has also influenced the recent pandemic spread of extended-spectrum cephalosporin resistance (3,4,18,28,29,34,44).…”
mentioning
confidence: 99%
“…Oteo et al recently reported that ESBLproducing E. coli isolates in Spain usually correspond to phylogroup A (40%), followed by group B1 (28%), group D (18%), and finally, group B2 (14%) (27). B2 is mainly associated with extraintestinal pathogenic strains from the community and is frequently overrepresented in ESBL studies (2,33). In our collection, B2 is represented in both community (all from urine samples) and hospital (two from urine, two from blood, and one from respiratory secretions) origins.…”
Section: Discussionmentioning
confidence: 99%